Snacking habits, nutritional status and physical activity of adolescents aged 13, 14 and 16 in Kelantan - Zainol, Nur Fatin (Pusat Pengajian Sains Kesihatan, 2017)
This study is about snacking habits, nutritional status and physical activity of adolescents aged 13, 14 and 16 in Kelantan. A total of 291 adolescents, 110 males (37.8%) and 181 females (62.2%) were randomly selected from four secondary schools within Kelantan. The main objective of this study was to determine the snacking habits among adolescents aged 13, 14 and 16 years old, to access nutritional status and physical activity of the respondents and to compare it between male and female. Besides, this study also determined the association between daily snacking frequency with nutritional status and physical activity. Questionnaires that included socio-demographic information, anthropometric information, snacking habits, main meals consumption and frequency of snack intake per week were used. The physical activity of adolescents were measured using Physical Activity Questionnaire for Adolescents (PAQ-A). All data obtained were analysed using Pearson Chi-Square test and Mann-Whitney test with p value < 0.05. Majority of respondents (43.0%) consumed snacks at least once per day. A total number of 193 respondents (66.3%) were afternoon snacker. The most popular snack foods and beverages among adolescents were sweet or candy, biscuits, caffeinated drinks and milk tea. Body Mass Index (BMI) value of respondents was compared with cut-off point by World Health Organization (WHO, 2007). Data indicated that most of respondents had normal BMI (Male 41.1%, Female 58.9%). Then, who was overweight, higher percentage was among female, obese male had higher percentage than female. Majority of respondents were in moderate physical activity (Male 66.4%, Female 56.9%). Males were more physically active than females (X2=17.294, p<0.001) with higher female respondents (39.8%) in low physical activity level category as compared with male (20.9%). The nutritional status and physical activity were significantly different between male and female respondents. However, there was no significant association between nutritional status and daily snacking frequency (X2=3.026, p=0.220) and there was no significant association between physical activity and daily snacking frequency (X2=2.316, p=0.314).